2012
DOI: 10.1038/onc.2012.209
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic B-Raf signaling in melanoma cells controls a network of microRNAs with combinatorial functions

Abstract: Over two-thirds of melanomas have activating mutations in B-Raf, leading to constitutive activation of the B-Raf/MKK/ERK signaling pathway. The most prevalent mutation, B-RafV600E, promotes cancer cell behavior through mechanisms that are still incompletely defined. Here, we used a sensitive microarray profiling platform to compare microRNA (miRNA) expression levels between primary melanocytes and B-RafV600E-positive melanoma cell lines, and between melanoma cells treated in the presence and absence of an MKK1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 39 publications
3
44
0
Order By: Relevance
“…Indeed, individual genetic variability as well as the heterogeneity of the tumors may hamper the identification of functionally relevant deregulated miRNAs. The generation of appropriate cell model systems might help to “read” expression profile data [40-42]. …”
Section: Discussionmentioning
confidence: 99%
“…Indeed, individual genetic variability as well as the heterogeneity of the tumors may hamper the identification of functionally relevant deregulated miRNAs. The generation of appropriate cell model systems might help to “read” expression profile data [40-42]. …”
Section: Discussionmentioning
confidence: 99%
“…Estimates of miRNA half-life range from 1 to Ͼ200 h in animal cells (60 -62), arguing that targets with extended kinetics are likely to be biologically relevant. In addition, measurements of intracellular miRNA concentrations show 60-to 250-fold increases in response to transfection of 15-50 nM exogenous miRNA (39,63,64), matching the more than 1000-fold changes in endogenous miRNAs quantified under varying cellular (e.g. disease) conditions (65,66).…”
Section: Discussionmentioning
confidence: 99%
“…WM239A cells derived from metastatic melanoma were labeled by SILAC with heavy (H) or light (L) isotopically-labeled ArgϩLys, and transfected with 50 nM of nontargeting (NT) miRNA or miR-22, previously identified as an miRNA whose expression is regulated by oncogenic mutant B-Raf signaling in melanoma (39). Proteins from whole cell lysate were trypsinized and the resulting peptides were analyzed by LC-MS/MS (Fig.…”
Section: Protein Abundance Changes In Response To Mir-22-mentioning
confidence: 99%
“…Changes in miRNAs expression levels are known to play a key-role in various human cancers (20,21), including melanoma (22). Gene-expression profiling studies previously showed that a network of miRNAs is controlled by BRAF/MEK/ ERK signaling (23). In this paper we identify a mechanism of drug resistance in BRAF mutated melanoma centered around a poorly characterized miRNA, miR-579-3p.…”
Section: Significancementioning
confidence: 95%
“…Significance Analysis of Microarrays performed on melanomas and normal melanocytes recently resulted in the identification of 32 differentially expressed miRNAs (41). Moreover a highly sensitive microarray profiling showed that a network of 420 miRNAs is controlled by B-Raf/MEK/ERK signaling (23). More recently, detailed investigations of individual microRNAs have demonstrated the involvement of miR-125b, miR-365, and miR-425 as tumor suppressors in metastatic melanoma, and of miR-3151 as oncomiR (refs.…”
Section: Mir-579-3p Is Down-regulated In Melanoma Patients Who Developedmentioning
confidence: 99%